The Relationship Of Self Control To Students Gadget Use - Niken Debora; Indah Sukmawati (Universitas Negeri Padang, 2021)
This research was animed to examine the corralation between self-control and student gadget use. This research is a quantitative study involving students in SMAN 1 Sungayang with a total sample of 245 students. The instrument used to collect data in this study was a questionnaire. Data were analyzed using the rank spearman correlation technique with help of the statistic product and service solution (SPSS) 22.0 program. These reasult indicate the correlation coefficient in this study is -0.062 and signifficant level of 0,335. This means that there is no correlation between sefl-control and gadget use. So, concluded that the higher the self-control, the lower the use of gadgets, and conversely the lower the self-control, the higher the use of gadgets.